2017
DOI: 10.4103/2229-516x.205819
|View full text |Cite
|
Sign up to set email alerts
|

Antepartum hemorrhage: A retrospective analysis from a northern nigerian teaching hospital

Abstract: Background:Antepartum hemorrhage (APH) contributes significantly to maternal and perinatal morbidity and mortality globally, particularly in the developing world like ours. Prevention, early detection, and prompt management cannot be overemphasized to significantly reduce the morbidity and mortality associated with this condition.Objectives:The study is aimed at determining the prevalence, etiology, sociodemographic characteristics, and the fetomaternal outcome of pregnancies complicated by APH in Aminu Kano T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
23
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 13 publications
14
23
4
1
Order By: Relevance
“…Out of these cases, placenta Previa was the leading cause constituting 76.8% of antepartum hemorrhage cases (16/1000 live births). Some studies agreed with our finding and in others, placental abruption was the leading cause [5]. The incidence of placenta Previa in our study was much higher than reported before.…”
Section: Discussionsupporting
confidence: 93%
“…Out of these cases, placenta Previa was the leading cause constituting 76.8% of antepartum hemorrhage cases (16/1000 live births). Some studies agreed with our finding and in others, placental abruption was the leading cause [5]. The incidence of placenta Previa in our study was much higher than reported before.…”
Section: Discussionsupporting
confidence: 93%
“…Thus early cesarean section was found to decrease the mortality in our study. 11,12 Another study from Peshawar in 2016 by Gul et al 13 reported the mean age of 29 ± 6.06 years.…”
Section: Resultsmentioning
confidence: 98%
“…However, these early signs often go unidentified due to lack of care, leading to obstetric hemorrhage accounting for 25-30% of all maternal deaths (Walfish et al, 2009, Say et al, 2014, Takai et al, 2017 . Likewise, early identification of pre-eclampsia, which is the second leading cause of maternal death (Say et al, 2014), can enable treatment (Bezerra Maia et al, 2012).…”
Section: Introductionmentioning
confidence: 99%